Identify The Urinary Bladder Cancer Patterns In Nasiriyah city / Thi-Qar Province – Iraq - mahdi, Mohammed; Mohammed. H. Alyasiri,; Saad Abdul Azeez Atiyah, (University of Thi-Qar Journal of Science, 2023)
This study aims to shed light on the generality types of urinary bladder cancer in the city of Nasiriyah / Thi-Qar Province – Iraq. The study includes cases that were registered in the Department of Pathology in Al-Hussein Teaching Hospital and Private Laboratories. Patient records were analyzed for information regarding age, sex, residence, and cancer type. A total of 114 sufferers of bladder cancer were obtained. The data taking period was from January 1, 2021 to April 30, 2022. Tumors were diagnosed mainly in the private laboratories of two consultant pathologists in Nasiriyah. The results showed 107 (93.86%) transitional cell carcinomas with a mean age of 47 years, in addition to 6 (5.26%) squamous cell carcinomas with a mean age of 69 years and 1 adenocarcinoma (0.88%) at the age of 51 years. Out of all cancer cases, males accounted for 74.56% whilst females accounted for 25.44%, indicating a male to female ratio of 4:1. Additionally, males showed a clear dominance in the totality of the histological grades. The age range with the highest number of cancer cases was between 70-79 years old (n = 37; 32.45%), while the age range with the lowest number of cases was between 23-39 years old (n = 3; 2.63%). The current study concluded that the majority types of bladder cancer in the city of Nasiriyah / Thi-Qar Province - Iraq are transitional cell carcinomas with an average age of 47 years. Among all cancers, males had the highest incidence.